Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1935
DOI: 10.1113/jphysiol.1935.sp003317
|View full text |Cite
|
Sign up to set email alerts
|

Afferent fibres from the abdomen in the vagus nerves

Abstract: EVIDENcE has recently been advanced of the existence of afferent fibres from the abdomen in the splanchnic nerves [Bain, Irving and McSwiney, 1935]. It is also believed that afferent fibres from the abdomen are present in the vagus nerves, but the evidence in support of the presence of these fibres is unsatisfactory, and in many instances the experimental results reported are contradictory. Thus on the one hand it is stated that there is no evidence for the presence of sensory fibres in the abdominal vagus ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1941
1941
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Since these demonstrations were made in decerebrate spinal cord pithed preparations the possibility that the reactions involved afferents which leave the vagus in the thorax and enter the thoracic spinal cord (Harper, McSwiney & Suffolk, 1935) has been avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these demonstrations were made in decerebrate spinal cord pithed preparations the possibility that the reactions involved afferents which leave the vagus in the thorax and enter the thoracic spinal cord (Harper, McSwiney & Suffolk, 1935) has been avoided.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement in gastro-oesophageal reactions of vago-vagal reflexes is further indicated by the demonstration of both excitatory and inhibitory responses to afferent vagal stimulation of the abdominal vagus nerve trunks. Since these demonstrations were made in decerebrate spinal cord pithed preparations the possibility that the reactions involved afferents which leave the vagus in the thorax and enter the thoracic spinal cord (Harper, McSwiney & Suffolk, 1935) has been avoided.…”
Section: Discussionmentioning
confidence: 99%
“…BY A. S. PAINTAL* From the Physiology Branch, Technical Development Establishment Laboratories, Kanpur, India (Received 22 April 1954) A number of investigators have shown that reflex respiratory, pupillary or vascular effects are produced by stimulating the central end of the vagi below the diaphragm (Brodie & Russell, 1900;Neumann, 1914;Carlson & Luckhardt, 1921;Harper, McSwiney & Suffolk, 1935), although these observations do not indicate that nerve fibres of the stomach are involved. However, Irving, McSwiney & Suffolk (1937) have shown clearly from a study of pupillary responses that sensory impulses in the vagus are produced when the stomach is distended.…”
mentioning
confidence: 99%
“…Some viscerotopic organization of the nodose ganglia has been observed in electrophysiological studies (145) but denied in histological studies that used horseradish peroxidase labeling (128). There has been one report of vagal afferent fibers leaving the main thoracic trunks and entering the spinal cord along with intercostal nerves (105).…”
Section: Pathways To the Central Nervous Systemmentioning
confidence: 99%